Kajian Semiotik Qashīdah Ghazl Karya Nizar Qabbani - Fika Hidayani; Am'mar Abdullah Arfan (Tsaqofah, 2021)
Poetry among Arabs is very important in its existence, because it can describe the life of the Arabs. One of the most prominent literary figures in the Arab world is Nizar Qabbani. Beside a poet, he is a Syrian Diplomat. His works talk a lot about love and women. Talk about women's feelings, defending women's rights and women's education at that time. In this research, we will analyze semiotically the meaning of the poem entitled Atuhibbunī consisting 21 verse. Poetry which taken from the internet site almubarak.net in 2006 is talking about woman. In analyzing the meaning, the researcher will use the Riffaterre meaning method, namely analyzing the indirectness of the expression and semiotic reading which consists of heuristic, retroactive, and hermeneutic.